Knockdown of Dehydrodolichyl Diphosphate Synthase in the Drosophila Retina Leads to a Unique Pattern of Retinal Degeneration - Brandwine, Tal; Ifrah, Reut; Bialistoky, Tzofia; Zaguri, Rachel; Rhodes-Mordov, Elisheva; Mizrahi-Meissonnier, Liliana; Sharon, Dror; Katanaev, Vladimir L.; Gerlitz, Offer; Minke, Baruch (Frontiers in Molecular Neuroscience, 2021)
Dehydrodolichyl diphosphate synthase (DHDDS) is a ubiquitously expressed enzyme that catalyzes cis-prenyl chain elongation to produce the poly-prenyl backbone of dolichol. It appears in all tissues including the nervous system and it is a highly conserved enzyme that can be found in all animal species. Individuals who have biallelic missense mutations in the DHDDS gene are presented with non-syndromic retinitis pigmentosa with unknown underlying mechanism. We have used the Drosophila model to compromise DHDDS ortholog gene (CG10778) in order to look for cellular and molecular mechanisms that, when defective, might be responsible for this retinal disease. The Gal4/UAS system was used to suppress the expression of CG10778 via RNAi-mediated-knockdown in various tissues. The resulting phenotypes were assessed using q-RT-PCR, transmission-electron-microscopy (TEM), electroretinogram, antibody staining and Western blot analysis. Targeted knockdown of CG10778-mRNA in the early embryo using the actin promoter or in the developing wings using the nub promoter resulted in lethality, or wings loss, respectively. Targeted expression of CG10778-RNAi using the glass multiple reporter (GMR)-Gal4 driver (GMR-DHDDS-RNAi) in the larva eye disc and pupal retina resulted in a complex phenotype: (a) TEM retinal sections revealed a unique pattern of retinal-degeneration, where photoreceptors R2 and R5 exhibited a nearly normal structure of their signaling-compartment (rhabdomere), but only at the region of the nucleus, while all other photoreceptors showed retinal degeneration at all regions. (b) Western blot analysis revealed a drastic reduction in rhodopsin levels in GMR-DHDDS-RNAi-flies and TEM sections showed an abnormal accumulation of endoplasmic reticulum (ER). To conclude, compromising DHDDS in the developing retina, while allowing formation of the retina, resulted in a unique pattern of retinal degeneration, characterized by a dramatic reduction in rhodopsin protein level and an abnormal accumulation of ER membranes in the photoreceptors cells, thus indicating that DHDDS is essential for normal retinal formation.